Loss, Commemoration, and Listening… For Yoko - Frohlick, Susan (Anthropologica, 2022)
In this exploratory piece, I draw from sound studies and the anthropology of sound to find my way in to a long overdue commemoration of a participant-interlocutor and friend who died in 2018. In thinking back on the significance of sound and listening in our evolving relationship, I work through my grief and loss. I offer two “listening stories” as a means to both honour Yoko and to reflect upon my own “listening habits, privilege and biases” (Robinson 2020, 72) that have implications personally as well as for anthropology more broadly.